Java Blues and Roots Music Festival: Borobudur Highland Event Branding Process Mix - Sylvia, Alya Salma; Putra, Rifki Rahmanda (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2023)
Borobudur Highland tourist destination is located in Purworejo Regency, Central Java Province which is managed by the Borobudur Authority Implementing Agency, as stipulated in Presidential Regulation Number 46 of 2017. The purpose of this research is to find out the process mix of the Java Blues and Roots Music Festival event. This research also examines the process mix at the Java Blues and Roots Music Festival event as a branding event for Borobudur Highland tourism destinations. The research method used is qualitative with data collection techniques of participatory observation, interviews, and documentation. The promotional strategy has been carried out by the management to introduce Borobudur Highland to the wider community through digital and non-digital in the form of advertisements, promotional videos, brochures, books, brochures, leaflets, and events. The organization of the Java Blues and Roots Music Festival event is a step by the manager to promote destinations through events to bring visits to Borobudur Highland. Through research on the process mix at the music festival event, several obstacles were still found regarding venue readiness and evaluation for managers if used as a tourist attraction. In addition, this research found that Borobudur Highland branding is still limited to getting 'brand awareness'.Java Blues and Roots Music Festival: Borobudur Highland Event Branding Process Mix